2005
DOI: 10.1086/430323
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic Anti‐Inflammatory Pathway Regulates the Host Response during Septic Peritonitis

Abstract: These data provide the first evidence, to our knowledge, of an important role of the vagus nerve in regulating the innate immune response to a severe bacterial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
225
5
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(249 citation statements)
references
References 31 publications
10
225
5
9
Order By: Relevance
“…In contrast, our study suggested that unilateral vagotomy not only aggravated the abnormality of ICM rats and increased the inducibility quotient of ventricular arrhythmias but also attenuated the effects of eliciting CAP. It was also reported that vagotomy attenuated the anti‐inflammatory effect of CAP and thereby enhanced cytokine release in response to LPS treatment 41, 42. Thus, vagotomy, performed in an ICM rat, increased the release of cytokines and collagens and altered the sympathetic/parasympathetic ratio, which served as a harmful role of ventricular arrhythmia.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, our study suggested that unilateral vagotomy not only aggravated the abnormality of ICM rats and increased the inducibility quotient of ventricular arrhythmias but also attenuated the effects of eliciting CAP. It was also reported that vagotomy attenuated the anti‐inflammatory effect of CAP and thereby enhanced cytokine release in response to LPS treatment 41, 42. Thus, vagotomy, performed in an ICM rat, increased the release of cytokines and collagens and altered the sympathetic/parasympathetic ratio, which served as a harmful role of ventricular arrhythmia.…”
Section: Discussionmentioning
confidence: 94%
“…Peritonitis was induced by i.p. injection of 10 4 CFU E. coli O18:K1, as described previously (14,15). In one experiment, 200 g of LPS (E. coli 0111:B4; SigmaAldrich) was injected i.p.…”
Section: Animals and Designmentioning
confidence: 99%
“…This pathway is controlled by brain muscarinic networks that depend on an intact vagus nerve to attenuate systemic cytokine production (5). Activation of the cholinergic antiinflammatory pathway, either by electrical stimulation of the vagus nerve or through pharmacological approaches, has been shown to significantly ameliorate cytokine-mediated disease models, including endotoxemia (2,6), sepsis (6,7), colitis (8), pancreatitis (9), and ischemia reperfusion (10,11).…”
mentioning
confidence: 99%